Coverage of Blood Vessels by Astrocytic Endfeet Is Reduced in Major Depressive Disorder - Rajkowska, Grazyna; Hughes, Jonathan; Stockmeier, Craig A.; Javier Miguel-Hidalgo, Jose; Maciag, Dorota (Biological psychiatry (1969), 2013)
Depression and cerebrovascular disease influence each other, according to clinical studies. Despite this evidence, no studies have investigated the relationship between major depressive disorder (MDD) and cerebrovascular disease at the cellular level. Astrocytic processes are a crucial interface between blood vessels and neurons, and astrocyte density is reduced in MDD. This study investigated the coverage of vessels by astrocyte endfeet in the prefrontal cortex in MDD. Thirteen pairs of MDD and nonpsychiatric control subjects were used for double immunofluorescent staining and confocal image analysis. Frozen sections of gray matter from orbitofrontal area 47 and white matter from the ventromedial prefrontal cortex were examined. Astrocytic processes (labeled with antibodies for aquaporin-4 (AQP4) or glial fibrillary acidic protein were co-localized with blood vessels (labeled with an antibody to collagen IV) to measure the coverage of vessel walls by astrocyte processes. The coverage of blood vessels by endfeet of AQP4-immunoreactive (IR) astrocytes was significantly reduced by 50% in subjects with MDD as compared with control subjects [analysis of covariance: F(1,23) = 5.161, p = .033]. This difference was detected in orbitofrontal gray matter but not in white matter. Conversely, the coverage of vessels by glial fibrillary acidic protein-IR processes did not significantly differ between the groups. A significant reduction in the coverage of gray matter vessels by AQP4-IR astrocyte processes in MDD suggests alterations in AQP4 functions such as regulation of water homeostasis, blood flow, glucose transport and metabolism, the blood-brain barrier, glutamate turnover, and synaptic plasticity.